Penerapan Pendekatan Matematika Realistik untuk Meningkatkan Kemampuan Komunikasi Matematis - Rodiana Lubis; Safaten Sudoh (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study aims to improve students’ mathematical communication skills, especially in integerarithmetic operations using the Realistic Mathematics Education (PMR) approach in Class VII-1 Madrasah Tsanawiyah Swasta Baharuddin Janjimauli Muaratais, Angkola Muaratais District. The type of research used is Classroom Action Research (CAR) using two cycles, and each cycle has 2 meetings. The subjects of this study were students of class VII-1 Madrasah Tsanawiyah Swasta Baharuddin Janjimauli Muaratais, Angkola Muaratais District which consisted of 14 male students and 9 female students. Based on the data from the research conducted, it was obtained the results of increasing students' mathematical communication skills in writing through tests. The results showed that the initial test of the number of students who completed was 7 students with a percentage of 30.43%. After implementing the realistic mathematical approach, there was an increase in students' mathematical communication skills at each meeting. Cycle I meeting 1 average of students who completed 66.08 with a percentage of completeness 43.47%, cycle I meeting 2 an average of students who completed 72.82 with a percentage of completeness 60.86%, cycle II meeting 1 an average of students who completed 77.17 with a percentage of completeness 73.91%, cycle II meeting 2 the average student who completed 81.74 with a percentage of completeness 86.95%.